2015
DOI: 10.1097/ccm.0000000000001085
|View full text |Cite
|
Sign up to set email alerts
|

New Insights Into Multicenter PICU Mortality Among Pediatric Hematopoietic Stem Cell Transplant Patients*

Abstract: Objectives Over 2,500 children undergo hematopoietic stem cell transplantation in the United States each year, and up to 35% require PICU support for life-threatening complications. PICU mortality has dropped from 85% to 44%, but interpretation is confounded by significant cohort heterogeneity. Reports conflict regarding outcomes for patients with different underlying hematopoietic stem cell transplantation indications, and the burden of infectious complications for these patients has not been evaluated. We ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
68
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 67 publications
(81 citation statements)
references
References 51 publications
11
68
0
Order By: Relevance
“…Cancer and HSCT have been associated with mortality since the first descriptions of ARDS in children (13, 30), and our recent work has shown that this continues to be true (31). The precise mechanisms responsible are multifactorial and may relate to pulmonary toxicity of chemotherapy, radiation therapy, opportunistic infections, and in the case of stem cell transplantation, alloreactivity in the setting of immune reconstitution (32). Of note, in the graphical representation of these models (Figure 1 and Figure 2), even cancer/HSCT patients with relatively low OI on Day 1 or Day 3 are at elevated risk for mortality, which may allude to intrinsic differences in their ARDS pathobiology, such as the slower progressive nature of lung disease in the setting of occult infection or pulmonary graft versus host disease.…”
Section: Discussionmentioning
confidence: 99%
“…Cancer and HSCT have been associated with mortality since the first descriptions of ARDS in children (13, 30), and our recent work has shown that this continues to be true (31). The precise mechanisms responsible are multifactorial and may relate to pulmonary toxicity of chemotherapy, radiation therapy, opportunistic infections, and in the case of stem cell transplantation, alloreactivity in the setting of immune reconstitution (32). Of note, in the graphical representation of these models (Figure 1 and Figure 2), even cancer/HSCT patients with relatively low OI on Day 1 or Day 3 are at elevated risk for mortality, which may allude to intrinsic differences in their ARDS pathobiology, such as the slower progressive nature of lung disease in the setting of occult infection or pulmonary graft versus host disease.…”
Section: Discussionmentioning
confidence: 99%
“…We also tested for relationships with a history of hematopoietic cellular transplantation (HCT), which we have previously shown to significantly impact pediatric ARDS outcomes and plasma biomarkers (2628). …”
Section: Methodsmentioning
confidence: 99%
“…While significant progress has been made in improving the safety of anti-neoplastic and transplantation-based therapies, the risk of infectious complications remains high (4). In particular, lower respiratory tract infections in children who have undergone HCT are associated with mortality rates exceeding 45% (5,6). Current microbiologic diagnostics are inadequate and fail to identify a pathogenic organism in over one third of such cases (7).…”
Section: Introductionmentioning
confidence: 99%